Simultaneous quantification of seven multi-class organic molecules by single-shot dilution differential pulse voltammetric calibration - Gonçalves, Daniel A.; Carmo, Jéssica S.; Zanon, Layne Taynara S.; Marangoni, Bruno S.; Cena, Cícero; Camara, Giuseppe A.; Donati, George L.; Trindade, Magno A.G. [UNESP] (Elsevier, 2022)
The contamination of water sources by anthropogenic activities is a topic of growing interest in the scientific community. Therefore, robust analytical techniques for the determination and quantification of multiple substances are needed, which often require complex and time-consuming procedures. In this context, we describe a univariate calibration method to determine emerging multi-class contaminants in different water sources. The instrumental setup is composed of a lab-made glass electrochemical cell with three electrodes: Pt counter, Ag/AgCl reference, and BDD working electrodes. With this system, we were able to simultaneously quantify tert-butylhydroquinone, acetaminophen, estrone, sulfamethoxazole, enrofloxacin, caffeine, and ibuprofen by differential pulse voltammetry. Only two calibration solutions are required for the Single-shot Dilution Differential Pulse Voltammetric Calibration (SSD-DP-VC) method described here, which can significantly improve sample throughput. Two robust univariate calibration strategies were also applied and compared with SSD-DP-VC. The new method is simple, fast, and comparable with traditional calibration methods, showing similar precision and accuracy for all determinations evaluated.
Keywords: Boron-doped diamond electrode; Differential pulse voltammetry; Dilution analysis; Keywords; Univariate calibration; Water analysis